Induced activation in accelerator components - Cristian Bungau; Adriana Bungau; Robert Cywinski; Roger Barlow; Thomas Robert Edgecock; Patrick Carlsson; Håkan Danared; Ferenc Mezei; Anne Ivalu Sander Holm; Søren Pape Møller; Heine Dølrath Thomsen (Physical Review Special Topics. Accelerators and Beams, 2014)
The residual activity induced in particle accelerators is a serious issue from the point of view of radiation safety as the long-lived radionuclides produced by fast or moderated neutrons and impact protons cause problems of radiation exposure for staff involved in the maintenance work and when decommissioning the facility. This paper presents activation studies of the magnets and collimators in the High Energy Beam Transport line of the European Spallation Source due to the backscattered neutrons from the target and also due to the direct proton interactions and their secondaries. An estimate of the radionuclide inventory and induced activation are predicted using the GEANT4 code.